The Retirement Behavior of Married Couples: Evidence From The Spouse's Allowance - Michael Baker (University of California, Department of Economics, 1999)
I examine the effects of the introduction of the Spouse's Allowance to the Canadian Income Security system on the retirement behavior of couples. This policy intervention provides an excellent opportunity to investigate how income security programs affect the timing of retirement. The structure of the Allowance also provides a view of how programs targeted at one spouse can affect the behavior of the other. Finally, conditional of the types of data available for this time period, the analysis considers the joint labor market decisions of couples. The results indicate that the introduction of the Allowance is associated with decreased employment rates and increased not in the labor force rates among eligible males. Eligible females did not share the rising employment rates over the 1970s experienced by their counterparts who were not eligible for the Spouse's Allowance.
Keywords: 330